Translinguando sentidos autoetnográficos críticos como professora imigrante venezuelana da perspectiva decolonial - Rosana Iriani Daza de Garcia (2022)
According to data from the "Ministry of Citizenship", Dourados (MS) is the third Brazilian municipality that received the most Venezuelan migrants through Operation Welcome. Among the effects of this flow to this city, in Mato Grosso do Sul, the growing number of Venezuelans enrolled in public schools and the challenge in training teachers to "welcome" these people stands out. The work accentuates my locus of enunciation (BHABHA, 1988), as a teacher and researcher, and it aims at interpreting interpret and analyzing the construction of autoethnographic meanings, (self)critical reflexivity in my social practice, that is, in my theoretical-practical pedagogy with students of Languages, by teaching a community course entitled "Spanish Language and Venezuelan Culture", from March to June 2021, at the Federal University of Grande Dourados (UFGD), in Dourados (MS) and in my trajectory as an immigrant. The methodology used was of a critical autoethnographic nature (SHORT; TURNER, TURNER, 2010 GRANT, 2013, ONO, 2017, TAKAKI, 2020). This decision permitted me to generate data, to confront them with my assumptions and experiences, with the emerging differences in the classroom, emphasizing my intersubjectivities, already informed by the chosen theories, regarding the apprehension of the dynamism of work. The research is located within the scope of the perspectives of critical literacy (CERVETTI, PARDALES, DAMICO, 2001, JANKS, 2010, LUKE, 2012, MENEZES DE SOUZA, 2010, 2011, MONTE MÓR, 2010, 2018; MONTE MÓR; MORGAN , 2014) inspired by Freire (2001, 2011), translanguaging (CANAGARAJAH, 2013, 2017, GARCÍA, 2009, GARCÍA; WEI, 2014, WEI, 2018, YIP; GARCÍA, 2018), "new" literacies (LANKSHEAR; KNOBEL, 2006, LANKSHEAR, 2007), epistemologies of the South (SOUSA SANTOS; MENEZES, 2010), affects and effects (BOLDT AND LEANDER, 2020), interculturalty (WALSH, 2006; 2009; 2012; 2018) coloniality (QUIJANO, 1992; DUSSEL, 2000) and decoloniality (MENEZES DE SOUZA, 2019, 2010, MIGNOLO, 2003, QUIJANO, 2000). The work focuses on linguistic-cultural education in the migratory context. The result of this doctoral research of a critical (auto)ethnographic nature highlights the innovation of scientific work both at the Federal University of Mato Grosso do Sul (UFMS) and at the Federal University of Grande Dourados (UFGD). This is because it goes through issues of language, Spanish teacher education in processes of host language. The result shows a learning experience with the other, the "socially vulnerable". This doctoral thesis enriches the possibilities of renegotiating knowledge, becoming an achievement as a Venezuelan immigrant teacher/student/researcher, who, even belonging to a group considered by society as a minority and subordinate, carried out actions with autonomy, creativity and criticism for “acolher” Brazilian teachers, employees and students. As a result, I hope that it can signal conditions for the active participation of immigrant teachers, like you, and that they are compatible with teaching and research that contemplate the emergence of the (self)critical construction of meaning. Collaborate with the scientific works of this country, expanding the perspectives of critical (auto)ethnographic critical linguistic education studies. Keywords: Southern and decolonial formation; Interculturality; Translanguaging; Critical (auto)ethnography.